The impact of Taekwondo instructors’ nonverbal communication on student engagement in liberal arts education: evidence from Chinese universities - Cheng, Long; Gu, Yimeng (Frontiers in Psychology, 2025)
BackgroundIn embodied disciplines like Taekwondo, instructor nonverbal communication (NVC) is a core pedagogical tool, yet its systemic impact on student engagement is often under-researched or treated as a monolithic outcome. This study analyzes the impact of Taekwondo instructors’ NVC on student engagement, operationalizing it as a multilevel construct comprising emotional, cognitive, and behavioral dimensions.MethodsA survey was conducted with 520 students enrolled in general education Taekwondo courses at five universities in China. Using a purposive sampling strategy, the study mapped Positive Emotions (as Emotional Engagement), Classroom Satisfaction (as Cognitive Engagement), and Recommendation Intention (as Behavioral Engagement) to examine their relationship with four NVC dimensions (appearance, auditory, body, and spatial language).ResultsThe analysis revealed a sequential process of engagement. First, Emotional Engagement (Positive Emotions) was significantly predicted by foundational NVC cues: visual, auditory, and body language. Second, Cognitive Engagement (Classroom Satisfaction) was similarly predicted by appearance, body, and auditory language. Third, high-level Behavioral Engagement (Recommendation Intention) was predicted by all four components, uniquely including spatial language.ConclusionThis study contributes a novel, tripartite model for assessing NVC’s total impact in sport pedagogy. We propose a sequential model where NVC first builds foundational trust and value (emotional/cognitive) and then, specifically through spatial cues, fosters the sense of belonging necessary for behavioral advocacy. These findings provide crucial data for the revitalization and teacher training of liberal arts Taekwondo classrooms.